2013
DOI: 10.1002/adsc.201300819
|View full text |Cite
|
Sign up to set email alerts
|

Combined Catalytic System of Scandium Triflate and Boronic Ester for Amide Bond Cleavage

Abstract: We have found that the combination of scandium with boronic ester enables the cleavage of amide bonds. Primary amides were converted to the corresponding esters in the presence of catalytic amounts of scandium triflate and boronic ester under mild and neutral conditions. This unique catalytic system can be applied to the deprotection of acetylaniline derivatives. In addition, control NMR experiments were carried out to examine the effect of the boronic esters.Keywords: amides; boron; scandium; solvolysis The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Conventionally, enzyme‐ or strong‐acid/base‐mediated C−N bond cleavage reactions of amides with alcohols generate huge amounts of undesired byproducts . Recently, catalytic C−N bond cleavage reactions, specifically the alcoholysis of amides into the corresponding esters, have received much attention and several examples have been reported . In general, the structural diversity of esters is relatively wide and they have found numerous applications in the chemical and pharmaceutical industry .…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, enzyme‐ or strong‐acid/base‐mediated C−N bond cleavage reactions of amides with alcohols generate huge amounts of undesired byproducts . Recently, catalytic C−N bond cleavage reactions, specifically the alcoholysis of amides into the corresponding esters, have received much attention and several examples have been reported . In general, the structural diversity of esters is relatively wide and they have found numerous applications in the chemical and pharmaceutical industry .…”
Section: Introductionmentioning
confidence: 99%
“…60,61 Berreau and Rivas reported the use of group 12 metal complexes with polydentate ligands for this reaction, mimicking the active site of peptidase enzymes, 62,63 showing that coordination of the metal to the carbonyl oxygen facilitates the nucleophilic attack of the alkoxide, leading to the formation of the ester. The same activation may be at the basis of the amide alcoholysis catalysed by simple transition metal salts [64][65][66][67][68] or lantanides salts and oxides. 64,69,70 Some examples of Cu-mediated alcoholysis of coordinated amides (i.e.…”
Section: Acyl Transfer As a Side Processmentioning
confidence: 99%
“…4). [25] The boronic ester was recovered unreacted after the reaction, and the parent boronic acid was totally inactive in the present system. On the basis of controlled NMR experiments, we found that alcohol-coordinated borane species cooperatively worked with Sc(OTf) 3 , to enhance the alcohol nucleophilicity through the formation of borate species.…”
Section: ð2þ ð3þmentioning
confidence: 66%